SEEPAGE MODELING IN EMBANKMENT DAMS WITH VARIOUS SUB SOIL CHARACTERISTICS - Almaretha Mevia Azizah Putri Iswanto; Wasis Wardoyo; Trihanyndio Rendy Satrya (Journal of Civil Engineering, 2022)
The earthfill dam might be built for all subsoils condition, however the common problems are the seepage flow and dam stability. This study uses numerical simulation model for seepage discharge and slope stability analysis. The characteristic of the dam is obtained from Tugu Dam, Trenggalek, while the subsoil data is varied for five soil types which are clay, silty clay, silt, silty sand, and sand. The first simulation analyze certain subsoil type during various water levels, while the second simulation analyze certain water level elevation during various soil types. Each simulation will be analyzed for seepage discharge and slope stability. The first simulation results show that seepage discharge and water level elevation have a logarithmic correlation with R2 > 0.75. The largest seepage discharge at 1.90 x 10-3 m3/s is sand soil, while the smallest is clay soil at 1.47 x 10-9 m3/s. The results of the second simulation show that the seepage discharge and saturated volumetric water content also have a logarithmic correlation. Based on these two simulations, the seepage discharge still meets the requirement since plotted below the average annual runoff, which is 1% of the 10-year re-flood discharge. The amount of re-flood discharge is calculated using the Nakayasu Synthetic Unit Hydrograph (SUH) which is 5.99 m3/s. The safety factor of slope stability is more than 1.2 which is considered as stable dam.